Reliable particle sizing in vaccine formulations using advanced dynamic light scattering - Bretz, Coline; Jauslin, Andrea; Leumann, Dario; Koch, Marius; Vaccaro, Andrea (Frontiers in Analytical Science, 2024)
Understanding the impact of lipid nanoparticle size on immunogenicity represents an important step for enabling the rapid development of novel vaccines against known or emergent diseases. Dynamic light scattering, also known as quasi-elastic light scattering or photon correlation spectroscopy, has established itself as an optimal analytical method to determine particle size due to its in-situ approach and fast measurements. However, its application to many systems of industrial relevance has been hindered due to artifacts arising from multiple scattering. Result interpretation becomes severely compromised depending on the concentration of the system and the size of the particles. In this context, strong sample dilution is often required, bringing additional uncertainties to the formulation development process. Here, we show how advanced dynamic light scattering technology can filter out multiple scattering from the signal and yield fully accurate sizing measurements regardless of the sample concentration. We illustrate this in a comparative study with standard dynamic light scattering using polystyrene beads as model suspension as well as a concentrated commercial lipid nanoparticle adjuvant (AddaVax TM ).